Penyebab Perceraian dan Akibat Hukumnya: Dalam Pemenuhan Hak-Hak Hidup Keluarga - Hardiansyah, Muhammad (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2025)
Marriage is a religious command in the context of worshiping Him for a lifetime. However, due to disharmony in the household, divorce becomes the last resort that couples may take, which is allowed but hated by Allah SWT. This research is conducted using a descriptive-qualitative approach through documentation study, referring to several questions, including: (1) What are the legal consequences of marriage?; (2) What are the causes of divorce?; (3) How does the divorce process occur?; and (4) What are the impacts of fulfilling the rights of each party? From these questions, the answers include: (1) the consequence of marriage is the unity of the bond between husband and wife into a single household bond; (2) the main cause of divorce is the disharmony in the household relationship; (3) The divorce process is conducted at the Religious Court; and (4) The fulfillment of the rights of each party will be protected by law.